SELECTIVITY OF FLUAZIFOP-P-BUTYL IN YOUNG COFFEE PLANTS - Voltolini, Giovani Belutti; Castanheira, Dalyse Toledo; Netto, Pedro Menicucci; Alecrim, Ademilson de Oliveira; Rezende, Tiago Teruel; Guimarães, Rubens José; de Oliveira, Adenilson Henrique (Coffee Science - ISSN 1984-3909, 2019)
Weed control is fundamental in coffee cultivation due to their big interference, competing with the crop for water, light and nutrients. Among the control methods used, chemical control is highlighted, as a function of its high efficiency and low cost. However, due to application failures, herbicide drift phytotoxicity is common. Aiming at the search for selective active ingredients in coffee plants, the objective of this study was to evaluate the selectivity of the active ingredient Fluazifop-p-butyl in young coffee plants, and its effects on plant morphology, anatomy and physiology. The experiment was carried out in a greenhouse, with ‘Topázio MG 1190’ coffee plants (Coffea arabica L.), cultivated in pots with a capacity of 11 L substrate. The statistical design was randomized block design (RBD), with four replications and four doses of the herbicide, making up 16 experimental plots. Each plot consisted of three plants. The treatments were: 0%; 50%; 100% and 200% of the recommended commercial dose of the herbicide Fluazifop-p-butyl. The evaluations were performed at 120 days after application of the treatments. Morphological, physiological and anatomical characteristics were evaluated. Regardless of the evaluated characteristic, there was no difference between the doses of the herbicide. There were no visual phytotoxicity symptoms in the young coffee plants that received the herbicide Fluazifop-p-butyl. The growth of the coffee plants, as well as the physiological and anatomical characteristics, were not altered due to the application of the herbicide Fluazifop-p-butyl.